Experimental study on the effect of drying temperature on the final quality of dried fish - Syuhada, Ahmad; Razali, Razali; Rizkia, Rizkia (Jurnal Polimesin, 2025)
The production of dried fish is a key community efforts to increase the economic value of fish in the Aceh region, with most product sold in traditional markets. To improve the community's economy, the quality of dried fish must be enhanced to meet the standards of modern markets. This research aims to improve the production system and quality of dried fish. The study examines the effect of drying temperature on the quality of dried fish by comparing two methods: constant drying temperature and gradual reduction. The constant drying temperature was set at 80°C, while the gradual reduction started at 80°C and decreased by 10°C every 2 hours until reaching 60°C. The results showed that the drying temperature significantly impacts the final quality of dried fish. Drying at a constant temperature of 80°C resulted in a harder texture and darker color of the dried fish compared to the gradual reduction method. This is due to the rapid heat and mass transfer processes causing case hardening in the fish, making its texture harder. This research provides valuable insights to improve the drying process and ensure the production of high-quality dried fish.